BAYESIAN ANALYSIS ON THE GROWTH TRAITS IN NELORE MOCHO CATTLE RAISED IN CERRADO BIOME (Veterinária Notícias, 2020)
The aim of this paper is estimate the (co)variances components in the genetic parameters to the growth traits in Nelore Mocho cattle, raised in Cerrado biome, using Bayesian statistics. The information obtained from 48,063 cattle, provenient of Nelore Mocho herd, born from 1987 to 2009, participant of Breeder and Research Nacional Association's (ANCP) Nelore Brazil Program. The standard weight in 120 (P120), 210 (P210), 365 (P365), 450 (P450) years old has been evaluated, the weight gain from the birth to the weaning (GPND) and the weight gain from weaning to yearling (GPDS). The (co)variances components and genetic parameters have been estimated under univariate analyses considering the Bayesian statistics animal model by the MTGSAM (Multiple Trait using Gibbs Sampler under Animal Model). The estimated values to direct heritability were from medium to high magnitude in standard weights (0.23 to 0.33) and the weight gain (0.18 and 0.24), in creates and recreates phase, respectively. These results indicate the genetic variability existence in Nelore Mocho herd to growth traits, showing effective genetic growth when using the direct selection of these features in genetic improvement programs.